2012
DOI: 10.1148/radiol.12111915
|View full text |Cite
|
Sign up to set email alerts
|

Sequential MR Imaging of Denervated and Reinnervated Skeletal Muscle as Correlated to Functional Outcome

Abstract: STIR MR imaging can be used to differentiate between denervated and reinnervated muscles for at least 12 months after nerve transection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
28
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 53 publications
(77 reference statements)
2
28
0
1
Order By: Relevance
“…Cranial nerve involvement is observed in approximately 15% of patients with CIDP 28. Thus, signal intensity of the sternocleidomastoid muscle might have been higher among patients with CIDP than in control patients in our study, because the denervated muscles display higher signal intensity on STIR images 29. This effect would make nerve-to-muscle CNR in patients with CIDP smaller than expected; hence our result that nerve-to-muscle CNR in the patients with CIDP had higher value seems valid.…”
Section: Discussionsupporting
confidence: 42%
“…Cranial nerve involvement is observed in approximately 15% of patients with CIDP 28. Thus, signal intensity of the sternocleidomastoid muscle might have been higher among patients with CIDP than in control patients in our study, because the denervated muscles display higher signal intensity on STIR images 29. This effect would make nerve-to-muscle CNR in patients with CIDP smaller than expected; hence our result that nerve-to-muscle CNR in the patients with CIDP had higher value seems valid.…”
Section: Discussionsupporting
confidence: 42%
“…Moreover, when taking into account quantitative mean muscle STIR signal intensity evaluation, and not semiquantitative scoring, it correlates with denervation severity. These results are in agreement with those obtained by Viddeleer et al, who found a significant negative correlation between the muscle STIR signal intensity and the MRC score [9] in patients with complete acute distal median or ulnar nerve transection, then surgical repair, followed by longitudinal muscle MRI. In their protocol, they chose to study only one region of interest, whereas we calculated mean signal intensity in each muscle of each section.…”
Section: Discussionsupporting
confidence: 93%
“…The majority of the studies on the interest of muscle MRI in peripheral neuropathy focused on severe acute neuropathies for which EMG sensitivity is high, and, therefore, muscle MRI was less useful. Unfortunately, the comparison of the two techniques is not available in the study performed by Viddeleer, et al [9] since EMG examination of their patients was not performed or not included in their study. Even fewer data are available for mild or chronic lesions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Acute/subacute denervation change manifests as increased T2-weighted signal in skeletal muscle without associated atrophy and fatty infiltration that follows the innervation of the muscles. [39][40][41][42][43] These T2-weighted signal alterations may be detectable as early as 48 hours after nerve injury. 41 Although this is an excellent tool, the pronator quadratus is a notable pitfall in the upper extremity.…”
Section: Gadolinium Contrast Sequencesmentioning
confidence: 99%